Diplomat in Khaki Major General Frank Ross McCoy and American Foreign Policy, 1898 -1949 - Bacevich, A. J. (University Press of Kansas, 1989)
Hailed by the New York Times as "one of the best soldiers this country has produced," Frank Ross McCoy was, throughout his distinguished career, much more than just a good soldier. As friend and confidant to such leaders as Theodore Roosevelt, Leonard Wood, and Henry Stimson, he disproves the standard view of the military before 1940 as having no role in American foreign policy. Instead, as A. J. Bacevich ably demonstrates, McCoy was intimately involved in the development of U.S. foreign relations from McKinley's administration to Truman's.McCoy began his military career with Leonard Wood in Cuba during the SpanishAmerican War. After the war, he and Wood (who became military governor) worked together to establish democratic reforms in Cuba. There followed for McCoy a succession of difficult and sometimes dangerous assignments: The Philippines (during the Moro uprising), Mexico, France (as combat commander during World War I), Turkey and Armenia, the Philippines again, Nicaragua (during the Sandino's guerrilla campaign), Bolivia and Paraguay, and China (with the Lytton Commission investigating Japan's invasion of Manchuria). Following a series of stateside appointments, McCoy served finally as chairman of the Far Eastern Commission, an international body created to determine the fate of postwar Japan.Based on exhaustive research in McCoy's personal papers and official records, Bacevich shows that McCoy's career provides a unique perspective both on American foreign policy and on civilmilitary relations.